Factors that influence growth in real estate investment : A survey of residential real estate in meru township, Kenya - Murithi, Margaret Karimi (Meru: Murithi Margaret Karimi, 2014)
This study focused on the factors that influenced growth in real estate investiments in Meru Township, between 2008 and 2012.The variable that were considered in the study were social amenities, finance, demand, and physical infrastructure. The study used descriptive research design to obtain information on the current status of the phenomenon. The target population was 783 real estate owners and simple size of 82 respondents was selected using stratified(each council ward constituted one strata) random, sampling techniques. The research employed self-administer d questionnaires to obtain the required information needed for the study.The data was processed and analyzed using statistical package for social sciences (SPSS) version 15.Descriptive, inferential statistics and binary logistic regression were used for analysis. The results presented in summary reports and tables. Research findings were used to answer research questions and recommendations based on the results of the study on factors that influenced growth of real estate investment were made.The findings indicated that 65.9% of the investors in Meru Township had experienced growth in real estate investment.Demands for housing and availability of social amenities were identified as significant determinants of growth of real estate investiment in Meru Township with a significance of 0.00 and 0.046 respectively at 95% level of confidence. Finance and physical infrastructure had minimal significance influence on growth in real estate investment with significance of 0.0574 and 0.702 respectively at 95% level of significance and therefore further research is recommended to investigate these findings and find out if finance and infrastructure work well on commercial real estate.An investor in real estate will be motivated to build more units ( demand for houses high) and where social amenities are adequate hence growth in real estate investment. The study recommends that real estate investors to venture into real estate complex that constitute rental houses, schools, hotels, medical clinics,shopping centre for risk minimization and return maximization
A Research Project submitted in partial fulfillment of the requirement for a degree of master of business administration in the school of business and economics of Meru University of Science and Technology.